Scale of clinical observation to valuate the third functional unit of the Luria theory: EOCL-1. - Ramos-Galarza, Carlos (2019)
Luria's brain organization model proposes the interaction of three functional units to understand the work performed by the human brain. The first of them is responsible for the regulation of tone and wakefulness. The second one to receive, process and store the information. The third, and of central interest of the investigation, is responsible for programming, executing and verifying mental activity. To evaluate this theory, a series of experimental neuropsychological tests have been developed, however, a scale has not been proposed that, based on the theoretical precepts on the third functional unit, allows to assess it based on the behaviors of the daily life of the human being. This research proposes a scale that will allow the clinician to assess the mental abilities associated with the ability to program, execute and verify the most complex form of mental activity; integrated in the third functional unit of Luria. The proposal is discussed, based on the benefit that is generated by having a scale that will allow to assess this theory, in the different environments where the individual develops through the action of the cerebral abilities of the third functional unit.